Topological defects in active liquid crystals. (September 2019) - Aranson, I S
Abstract: A wide class of nonequilibrium systems comprising interacting self-propelled agents is termed active matter. The most relevant examples include suspensions of microscopic swimming organisms (bacteria, sperm cells, or unicellular algae), synthetic catalytic nanomotors, colloidal self-propelled Janus particles, and even macroscopic bird flocks, fish schools, or human crowds. The simplest and most studied realization of active matter is a suspension of microscopic swimmers, such as motile microorganisms or self-phoretic colloids. A liquid crystal, a highly-structured anisotropic environment with local molecular ordering 'doped' by a small amount of active component represents an interesting class of nonequilibrium materials with novel optical and mechanical properties. Singularities of local molecular orientation, or topological defects, play an important role in the spatiotemporal organization of active liquid crystals. This study surveys the most recent experimental and theoretical advances in the field of active liquid crystals and highlights connections with other nonequilibrium physical and biological systems.